Nutritional status and age of menarche in adolescent girls in urban and rural area schools - D., Ramamani; Rajendiran, Ramyaa; Kannan, Iyanar (International Journal of Contemporary Pediatrics, 2020)
Background: There are various factors that influences the age of menarche which includes genetic, nutritional status, socioeconomic status and environmental conditions. Further it has also proved that the malnutrition has delayed the age of menarche. Thus, the present study focuses on the study of relation between the nutritional status and age of menarche among the adolescent girls in a rural and urban area in Tamil Nadu, India. Methods: It is a community based cross-sectional study done in the adolescent girls of age between 11 to 15 years studying in school in the city of Chennai, India and surrounding rural areas. A total of 602 post-menarcheal adolescent girls were included in the study. The participants who were post-menarcheal were asked to recall the year and month of menarche and was noted. To assess the nutritional status, the parameters weight, height and waist circumference were determined. Results: The association between the age of menarche and BMI was studied. The study showed that there was an association with a Pearson coefficient (r) value of - 0.252 which is statistically significant (p˂0.001). The association between the age of menarche and waist to height ratio was studied. The study showed that there was an association with a Pearson coefficient (r) value of - 0.261 which is statistically significant (p˂0.001). Conclusions: This study has confirmed that the nutritional status has association with the age of menarche and is the contribution to the reduction in the mean of age of menarche in this geographical area.